Impact of liquid sublingual immunotherapy on asthma onset and progression in patients with allergic rhinitis: a nationwide population-based study (EfficAPSI study)Research in context - Pascal Demoly; Mathieu Molimard; Jean-François Bergmann; Bertrand Delaisi; Amandine Gouverneur; Jade Vadel; Cédric Collin; Laurence Girard; Silvia Scurati; Philippe Devillier (Elsevier, 2024)
Summary: Background: The only disease-modifying treatment currently available for allergic rhinitis (AR) is allergen immunotherapy (AIT). The main objective of the EfficAPSI real-world study (RWS) was to evaluate the impact of liquid sublingual immunotherapy (SLIT-liquid) on asthma onset and evolution in AR patients. Methods: An analysis with propensity score weighting was performed using the EfficAPSI cohort, comparing patients dispensed SLIT-liquid with patients dispensed AR symptomatic medication with no history of AIT (controls). Index date corresponded to the first dispensation of either treatment. The sensitive definition of asthma event considered the first asthma drug dispensation, hospitalisation or long-term disease (LTD) for asthma, the specific one omitted drug dispensation and the combined one considered omalizumab or three ICS ± LABA dispensation, hospitalisation or LTD. In patients with pre-existing asthma, the GINA treatment step-up evolution was analysed. Findings: In this cohort including 112,492 SLIT-liquid and 333,082 controls, SLIT-liquid exposure was associated with a significant lower risk of asthma onset vs. control, according to all definitions (combined: HR [95% CI] = 0.62 [0.60-0.63], sensitive: 0.77 [0.76-0.78], and specific: 0.67 [0.61-0.72]). Exposure to SLIT was associated with a one-third reduction in GINA step-up regardless baseline steps. Interpretation: In this national RWS with the largest number of person-years of follow-up to date in the field of AIT, SLIT-liquid was associated with a significant reduction in the risk of asthma onset or worsening. The use of three definitions (sensitive or specific) and GINA step-up reinforced the rigorous methodology, substantiating SLIT-liquid evidence as a causal treatment option for patients with respiratory allergies. Funding: Stallergenes Greer.